Atividades antioxidante, alelopática e antigenotóxica do exopolissacarídeo carboximetilado botriosferana - Gervásio, Suiany Vitorino (2019)
Secondary metabolites constitute an important part of the plants. Present protection function,assist in environmental responses and adaptation of plants to the environment. Its chemical composition is what favors the activities performed by secondary metabolites and enables its most diverse applications, whether for the treatment of diseases with the direct use of plants or production for industry. In search of new sources of secondary metabolites, the algae and fungi presented themselves as prominent groups, being used because of how ease is the production of these metabolites; without requiring large spaces and investments. Among the fungi, the genus Botryospaheria, known to cause diseases in plants, houses the species Botryosphaeriarhodina, which causes eucalyptus cancer, a promoter of fruit rot and is known for the production ofbotriosferana, a polysaccharide producedextracellularly, of type ß-glucana with type ß-(1 ? 3.1 ? 6) links and of low solubility. Botriosferanapresents antioxidant activity as well ashypocholesterolemic, antimutagenic, antifungal and antiviral activity. Aiming to potentialize these activities this molecule has undergone a structural alteration, carboxymethylation, where the number of branches is increased and therefore also its solubility. To verify that the increase in solubility has altered its activity, analyses of the antioxidants were performed by methods of DDPH, Abts, Frap and Iron chelating2+as well as the allelopathic activityin the test systems Allium Strain and Lactuca sativa, the cellular viability of human lymphocytes and sarcoma 180 by the MTT methodand the evaluation of mutagenic activity and antimutagenic in mice. The carboxymethylated botriosferana presented antioxidant activity only in two methods, DPPH and iron chelating, not presenting anyallelopathicactivity. Increased cell viability of lymphocytes, mainly under 48h of exposure, and was selective to decrease the cell viability of 180 sarcoma under 48h of exposure. It did not present mutagenic activity, but was antimutagenic, considerably decreasing the micronuclei values compared to positive control. The results obtained indicate that the structural alteration maintained the activities previously described and which were reassessed by comparing the reduction of damage caused by cyclophosphamide, there is an indication that the structural change potentiated this activity of the carboxymethylatedbotriosferana. When considering all the activities performed by botriosferana, it is possible to observe its potential application as an adjuvant for the treatment of chronic non- communicable diseases, such as hypercholesterolemia, and also for the treatment of cancer.